2017
DOI: 10.1016/j.trci.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traumatic brain injury and posttraumatic stress disorder on development of Alzheimer's disease in Vietnam Veterans using the Alzheimer's Disease Neuroimaging Initiative: Preliminary report

Abstract: IntroductionTraumatic brain injury (TBI) and posttraumatic stress disorder (PTSD) have previously been reported to be associated with increased risk of Alzheimer's disease (AD). We are using biomarkers to study Vietnam Veterans with/without mild cognitive impairment with a history of at least one TBI and/or ongoing PTSD to determine whether these contribute to the development of AD.MethodsPotential subjects identified by Veterans Administration records underwent an initial telephone screen. Consented subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 106 publications
3
80
1
Order By: Relevance
“…The currently largest neuroimaging study to include a focus on PTSD, ''ENIGMA-Enhancing Neuroimaging Genetics through Metaanalysis,'' recently found smaller hippocampal volumes in PTSD subjects than in traumaexposed control subjects (49), an effect that remained highly significant after adjustment for multiple comparisons. Some studies have also reported diminished hippocampal metabolism and cerebral blood flow associated with PTSD; but although PTSD patients can experience cognitive dysfunction and are at increased risk for development of AD, its associated pathology appears to be distinct from AD-related pathology with respect to medial temporal atrophy and amyloid positivity, when compared with suitable control subjects (50,51). Since exposure to traumatic events does not always lead to development of PTSD, it has been postulated that functional and structural abnormalities of the hippocampus may predispose an individual to PTSD (52).…”
Section: Hippocampusmentioning
confidence: 99%
“…The currently largest neuroimaging study to include a focus on PTSD, ''ENIGMA-Enhancing Neuroimaging Genetics through Metaanalysis,'' recently found smaller hippocampal volumes in PTSD subjects than in traumaexposed control subjects (49), an effect that remained highly significant after adjustment for multiple comparisons. Some studies have also reported diminished hippocampal metabolism and cerebral blood flow associated with PTSD; but although PTSD patients can experience cognitive dysfunction and are at increased risk for development of AD, its associated pathology appears to be distinct from AD-related pathology with respect to medial temporal atrophy and amyloid positivity, when compared with suitable control subjects (50,51). Since exposure to traumatic events does not always lead to development of PTSD, it has been postulated that functional and structural abnormalities of the hippocampus may predispose an individual to PTSD (52).…”
Section: Hippocampusmentioning
confidence: 99%
“…Both studies circumvented the limitation of self-reported TBI in cognitively impaired participants—one used self-reported TBI with loss of consciousness collected at a time when participants were known to be cognitively intact, 16 and the other used medical records information to document TBI exposure. 17 Likewise, neither study relied solely on clinical diagnosis of dementia and AD, but augmented diagnosis with neuropathology evaluations 16 or MRI and florbetapir PET scans. 17 …”
mentioning
confidence: 99%
“…These changes are described as reduced hippocampal volumes (Childress et al 2013;Rafferty et al 2018;Veitch et al 2013;Weiner et al 2014;Yaffe et al 2010), reduced cognitive reserve (Qureshi et al 2010;Rafferty et al 2018;Veitch et al 2013;Weiner et al 2013;Yaffe et al 2010), or inflammatory response Rafferty et al 2018;Yaffe et al 2010). Weiner et al (2017) studied Vietnam veterans to determine whether a diagnosis of PTSD increased the risk of dementia. Preliminary findings suggest that there was no evidence that PTSD neurological changes were related to biomarkers for dementia.…”
Section: Theme 2: Aetiology Underlying the Relationship Between Ptsd mentioning
confidence: 99%